An analysis of risk factors for visceral disseminated varicella in children - Guo, Shuai; Guo, Qin; Wan, Chaomin (Frontiers in Pediatrics, 2024)
Background: Visceral disseminated varicella has internal organ involvement, and complications such as encephalitis, hepatitis, and coagulation disorders threaten the patient's life. We aimed to analyze the risk factors for visceral disseminated varicella to help identify patients at high risk of visceral disseminated varicella early. Methods: Reviewed the medical records of children hospitalized with varicella. The data covered demographics, clinical manifestations, auxiliary examinations, treatments, and outcomes. Logistic regression was used to analyze risk factors. Results: Multivariate logistic regression analysis showed that abdominal pain (OR 20.451, 95%CI 1.637-255.548), increased CRP (OR 12.794, 95%CI 1.820-89.937), increased ALT (OR 7.453, 95%CI 1.624-34.206), and the time between onset and antiviral therapy more than 7 days (OR 12.451, 95%CI 1.569-98.810) were independent risk factors for visceral disseminated varicella. Conclusions: Patients with varicella who have these factors need to be monitored for the risk of developing visceral disseminated varicella, and timely antiviral therapy is necessary.